E-111 Cytokine registry database of stroke patients (CRISP). (22nd July 2018) - Zafar, A; Ikram, A; Farooqui, M; Quadri, S; Gonzalez, J; Ortega, S; Calder, C; Leira, E
Abstract : Purpose: The aim of this registry is to identify molecular biomarkers involve in the process after stroke and determine their relationship and clinical usefulness as potential biomarkers in stroke patients. Study design: This is a prospective patient registry (NCT03297827 ). Patients with ischemic and hemorrhagic stroke diagnosis will be recruited on admission to the University of New Mexico Hospital. Measurement of cytokines from two sets of serum and urine samples will be done on the admission and after 24 hours. Serum cytokine levels and inflammatory markers (interleukin-33, IL-37, IL-36, IL-4, IL-6, IL-10, IL-17, IL-23, IL-1, TNF, PDGF, VEGFM TNFa, ANNULIN, MMP-9, MMP-12, NFk-B levels plus metabolic products like MPO and glial factors: GMF, SI000B and GM6001) will be identified and evaluated using ELISA-PCR assays. Twenty-five percent of the total stroke patient serum samples will be matched by appropriate controls to confirm the level changes in stroke patients. Inclusion Criteria: 1. Adult Male/Female patients ages>18 years old 2. Patients whose standard stroke admission order sets are obtained for clinical care. 3. Patients with a history of MS may be included for future subanalysis. Exclusion Criteria: 1. History of prior stroke or any other neurodegenerative or neuroinflammatory disease except MS. 2. Individuals ages<18 year 3. Pregnant women 4. Prisoners. Results: The registry will enroll 600 participants. Results will be reported and shared on https://clinicaltrials.gov/ct2/show/NCT03297827 . Conclusion: The CRISP registry will give us understanding of the pertinent cytokines and inflammatory molecules involve in the process of stroke. These molecules can serve as biomarkers in the clinical management for acute stroke patients. Disclosures: A. Zafar: None. A. Ikram: None. M. Farooqui: None. S. Quadri: None. J. Gonzalez: None. S. Ortega: None. C. Calder: None. E. Leira: None.